Improving the scientific support for strategic planning in the Republic of Kazakhstan - Zhashkenova, R.B.; Nakipova, G.N.; Denisov, I.V.; Omarova, A.T.; Legostayeva, A.A. (BUKETOV BUSINESS REVIEW, 2020)
Object: The article discusses the features of scientific support for strategic planning in the Republic of Kazakhstan, which are necessary conditions for solving problems in the field of building the digital economy of Kazakhstan. Strategic planning in all hierarchical structures of government, both at the national and territorial, sectoral levels, in the activities of absolute common companies and business organizations. In accordance with strategic planning, all the coordinates of the entire state planning system. Methods: Authors and analytical materials based on educational, scientific, technical and innovative processes that lead to Kazakhstan. Based on the construction of regression models, it was found that the number of organizations engaged in research and development, and the volume of government spending on higher and postgraduate education affect the volume of internal research and development costs. Findings: It is recommended to improve scientific support for the realization of educational government program. Conclusions: In the process of the study, conclusions were drawn and recommendations were given, a way to provide assistance in providing a more advanced system of scientific support for strategic planning, necessary for solving urgent economic and social problems of the Republic of Kazakhstan.